FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR KAKAO PROVINSI LAMPUNG - Widuri Prameswita; R. Hanung Ismono; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
Lampung Province is the fourth cocoa producer in Indonesia after North Sumatra, West Sumatera, and Aceh. Lampung Province cocoa trade is large because the demand for its export and export price are relatively high. This study aims to determine the factors that influence the volume of cocoa exports and determine the impact of cocoa export tax rates (taxe exports) in Lampung Province. This study used both descriptive and quantitative analysis methods in which data was obtained from the relevant authorities as secondary data for 20 years, starting from 1993 to 2012. The research data was analyzed by SPSS 16.0 program for window. For purposes of data analysis and hypothesis testing proposed, used the method of”econometrics”. The results of this study showed that 1) the factors that significantly affected the export volume of cocoa in Lampung Province was the volume of cocoa production, cocoa export price (ICCO),interest rate, domestic price of cocoa and tariffs out (export tax) cocoa and 2) the impact after rising tariffs out (export taxes) would reduce the volume of cocoa exports in Lampung Province.Keywords : international trade, cacao, exports, export tarrif, export volume